Thinking about the Holocaust : after half a century - Rosenfeld, Alvin H. (Alvin Hirsch), 1938- (Jewish literature and culture., 1997)
"Thirteen distinguished scholars examine the representation and reception of the Holocaust within a range of national settings and generic forms. The authors draw on historical writing, testimonial literature, monuments and memorials, theological reflections, and documentary and imaginative poetry, prose, film, and drama to assess both the impact of the Holocaust on postwar consciousness and the impact of contemporary modes of scholarship on our understanding of the Holocaust itself."--Jacket